A Study on the Effect of Toroidal Propeller Parameters on Efficiency and Thrust - Ji Wu; Qingchun Wang; Hugh Deasy; Junyu Hang (Energies)
This paper delves into the effects of a toroidal propeller’s geometrical characteristics on its thrust and efficiency. The focus is on three distinct numerical distributions: the outward inclination angle, the pitch angle, and the number of blades. The Reynolds-Averaged Navier–Stokes (RANS) method is employed to analyze the propeller’s open-water performance, taking into account cavitation flow, and a test bed was constructed to verify the rationality of CFD simulation. The findings reveal that the toroidal propeller’s efficiency and thrust coefficient initially increase with the outward inclination angle, followed by a decline; the angle of maximum efficiency is identified at 23.25°. A reduction in the pitch angle leads to a temporary rise in efficiency, which subsequently falls, accompanied by a continuous decrease in the thrust coefficient. The optimal selection angle should consider this to prevent negative thrust at lower advance coefficients, which could further impact overall efficiency. An increased number of blades elevates the thrust coefficient and reduces the force on each blade, yet has a minimal effect on efficiency. Additionally, the orthogonal test method was utilized to explore the interactions between these three parameters. The outcomes indicate that, in terms of final power, there is no significant interaction among the three parameters under investigation. However, notable interactions are observed between the pitch angle and the number of blades, the outward inclination angle and the pitch angle, and the outward inclination angle and the number of blades. Consequently, the study’s findings facilitate the selection of parameter combinations that yield higher efficiency or thrust coefficients.